Pengaruh Good Corporate Governance Terhadap Nilai Perusahaan Pada Perusahaan Pertambangan Yang Terdaftar Di Bursa Efek Indonesia Tahun 2017-2020 - Wahyu Gusriandari; Mega Rahmi; Yosep Eka Putra (JURNAL PUNDI, 2022)
The main problem in this research is the weak implementation of Good Corporate Governance in mining companies due to selfish interests and the neglect of shareholders' interests so that fraud will have an impact on company value. The purpose of this study is to determine the effect of managerial ownership, independent commissioners and audit committees on firm value. The type of research used is ex post facto with a quantitative approach, the data sources used in this research are secondary data sources. Secondary data taken from the financial statements of mining companies listed on the Indonesia Stock Exchange in 2017-2020 through the official website of the Indonesia Stock Exchange www.idx.co.id. The data analysis technique in this study uses the Classical Assumption Test, to test the hypothesis using multiple linear analysis, T-test and F-Test and Determination Test.